TULIP: a randomised controlled trial of surgical versus non-surgical treatment of lateral compression injuries of the pelvis with complete sacral fractures (LC1) in the non-fragility fracture patient—a feasibility study protocol. Issue 2 (10th February 2020) - Barnfield, Steven; Ingram, Jenny; Halliday, Ruth; Griffin, Xavier; Greenwood, Rosemary; Kandiyali, Rebecca; Thompson, Julian; Glynn, Joel; Beasant, Lucy; McArthur, John; Bates, Peter; Acharya, Mehool
Abstract : Introduction: Lateral compression type 1 (LC1) pelvic fractures are the most common type of pelvic fracture. The majority of LC1 fractures are considered stable. Fractures where a complete sacral fracture is present increases the degree of potential instability and have the potential to displace over time. Non-operative management of these unstable fractures may involve restricted weight bearing and significant rehabilitation. Frequent monitoring with X-rays is also necessary for displacement of the fracture. Operative stabilisation of these fractures may be appropriate to prevent displacement of the fracture. This may allow patients to mobilise pain-free, quicker. Methods and analysis: The study is a feasibility study to inform the design of a full definitive randomised controlled trial to guide the most appropriate management of these injuries. Participants will be recruited from major trauma centres and randomly allocated to either operative or non-operative management of their injuries. A variety of outcome instruments, measuring health-related quality of life, functional outcome and pain, will be completed at several time points up to 12 months post injury. Qualitative interviews will be undertaken with participants to explore their views of the treatments under investigation and trial processes. Eligibility and recruitment to the study will be analysed to inform the feasibility of a definitive trial. Completion rates of the measurement instruments will be assessed, as well as their sensitivity to change and the presence of floor or ceiling effects in this population, to inform the choice of the primary outcome for a definitive trial. Ethics and dissemination: Ethical approval for the study was given by the South West—Central Bristol NHS Research Ethics Committee on 2nd July 2018 (Ref; 18/SW/0135). The study will be reported in relevant specialist journals and through presentation at specialist conferences. Trial registration number: ISRCTN10649958